Vitamin D Status in Cattle with Malignant Catarrhal Fever - Dabak, Murat; Dabak, Durrin Ozlem; Karapinar, Tolga; Bulut, Hakan (Japan Soc Vet Sci, 2012)
The aim of the present study was to determine the vitamin D status in cattle with malignant catarrhal lever (MM. Twelve cattle diagnosed as MCF and 6 healthy cattle (controls) were used in the study. Serum 1,25-dihydroxyvitamin D-3 (1,25-D). 25-hydroxyvitamin D-3(25-D), calcium, phosphorus and parathyroid hormone (PTH) levels were determined as 96.83 pg/ml, 30.0 ng/ml, 2.19 mmol/l, 1.57 mmol/l and 15.21 pg/ml in MCF group and 42.33 pg/ml, 37.0 ng/ml, 2.43 mmol/l, 1.96 mmol/l and 36.08 mu g/ml in controls, respectively. Although serum 1,25-D level in the MCF group was increased (P<0.01), serum calcium (P<0.01) and PTH (P<0.05) levels were decreased compared to the controls. The results suggest that there might be an interaction between vitamin D status and MCF.
Keywords: 1,25-dihydroxyvitamin D3; malignant catarrhal fever; ovine herpervirus-2; viral infection; vitamin D